A review on peening processes and its effect on surfaces - Tariq, Syed Qutoba; Asmelash, Mebrahitom; Saptaji, Kushendarsyah; Azmir, Azhari (Springer, 2022)
Surface treatment methods are widely used in various industries to improve the material performance and change their physical properties. The methods can be categorised according to the nature of the operation as mechanical, chemical, electrochemical and case hardening processes. Mechanical surface treatment methods are mainly utilised to add compressive residual stresses in surface layers thus usually improving the life of engineering components. Among various mechanical surface treatment methods, peening process is common in treatment nature by treating the surface using mechanical means. Three peening processes, namely shot peening (SP), laser shock peening (LSP) and waterjet peening (WJP) are selected to be the focus of the present paper due to their similarity based on impulsive effect to the surface by the input force through unguided tools in repetitive irregular manner without any oscillating or vibrating movement of tools. A comprehensive review is presented to discuss each of the peening processes and their effects on the surface integrity in terms of the topography, mechanical properties and microstructural changes. The investigation includes the discussion on the existing advantages, disadvantages and technological barriers of peening technologies for industrial applications. Detailed examples of recent advances in the peening methods are also discussed. The results show that the SP method produces more roughness as compared to LSP and WJP methods. However, fatigue strength is better without considerable changes in roughness and corrosion after LSP and WJP treatments. It can be concluded that the peening processes can improve the material performance with acceptable qualities for in-service application in industries.